Optoelectronic frequency response measurement using standard Mach-Zehnder modulator - Tangmala,T. (2015)
We demonstrate frequency response measurement technique of photodiodes using standard Mach-Zehnder Modulator (MZM). The technique is based on heterodyne detection principle where two-tone light, whose frequency separation is in Microwave frequency range, is used to stimulate the photodiode. The MZM, with typical on-off extinction ratio of 30 dB in optical domain, is used to generate two-tone light, instead of 50 dB extinction ratio of the previously proposed high ER MZM system. The converted RF signal shows extinction ratio of 40 dB, thus accurate power of the required component can be measured using a wideband RF power sensor. The measured frequency responses of two tested photodiodes indicate agreement with their specifications. © 2012 IEEE.